Iatrogenic Cushing Syndrome Secondary to Ritonavir-Epidural Triamcinolone Interaction: An Illustrative Case and Review - Sapna Sadarangani; Melody L. Berg; William Mauck; Stacey Rizza (Interdisciplinary Perspectives on Infectious Diseases)
HIV positive patients on ritonavir-containing antiretroviral therapy (ART) can develop iatrogenic Cushing syndrome (IACS) and adrenal insufficiency as a result of drug-drug interactions with inhaled or intranasal glucocorticoid therapy. Reports related to epidural triamcinolone injections are relatively uncommon but increasingly reported. We describe a 48-year-old woman with immunologically and virologically well-controlled HIV on ritonavir-based ART, who developed headache, dizziness, and candida and herpes simplex virus (HSV) ulcerative esophagitis 7 days after receiving an epidural triamcinolone injection for cervical radicular pain. Iatrogenic Cushing syndrome and relative adrenal insufficiency were suspected and proven. The patient’s ART was changed to a non-HIV protease inhibitor- (PI-) containing program, her symptoms improved, and she did not require hydrocortisone replacement. In this paper, we review the literature on IACS and relative secondary adrenal insufficiency from epidural triamcinolone injections in HIV patients on ritonavir-containing ART regimens. A high index of clinical suspicion is needed for diagnosis. Prevention of drug-drug interactions by taking a thorough medication history for patients on ritonavir-containing ART regimens before prescribing any form of corticosteroid is crucial and effective and sustained interdisciplinary communication in the care of such patients.